"Doing school in spite of everything": reflections from an extension training experience in the COVID-19 pandemic (Cuadernos de Extensión Universitaria de la UNLPam, 2023)
This paper critically addresses the continuing education course of the UNC Extension Secretary called "Between school and home: Experiences from neighborhood school support for the accompaniment of educational trajectories in times of pandemic". The general objective is to reason about the pedagogical and political challenges and potentials that this experience presented. To this end, from different analyitcal persepectives-community strategies for the support of educational trajectories, the presence/absence of the State, the connection/disconnection in virtual education scenarios, among others- we will approach the main discussions that arose from the dialogue of knowledge between different subjects that participate in the educational process of young people and children. To conclude, we will try to think how the experience and the resulting productions have a great potential to build an approach to educational issues through the integrality of university functions.
Keywords: school; community educational spaces; pandemic; university extension; integrality